Determining the relationship between stigmatization and social support in tuberculosis patients - Polat, Hatice; Turan, Gulcan Bahcecioglu; Tan, Mehtap (Elsevier, 2024)
Background & Aim: It is aimed to analyze the relationship between stigmatization levels and social support perceptions of tuberculosis patients. Methods & Materials: Research data are collected using socio-demographic information form, Stigmatization Scale in Patients with Tuberculosis and Multidimensional Social Support Scale. Results: 85.5 % of the patients have said that there are no other tuberculosis patients in their families. 83.9 % of the patients have stated that they did not tell anyone that they had tuberculosis. The results of the study show that patients with tuberculosis faced stigmatization, that their score from the scale is at a moderate level [mean:88.0 +/- 10.33], and they got a moderate score [mean:54.19 +/- 14.07] on the social support perception scale. It is determined that there is a negative relationship between social support perception and stigmatization. It is determined that tuberculosis patients experienced medium level of stigmatization. It is determined that their social support perception is at a medium level. Conclusion: Stigmatization level is found to be significantly higher in individuals whose support from family, friends and a significant other in their life decreased. In order to reduce stigmatization in patients with tuberculosis, it may be recommended to increase the awareness of the society about the disease.
20th Annual Congress of the Turkish-Thoracic-Society -- APR 05-09, 2017 -- Antalya, TURKEY
Keywords: Exclusion; Labeling; Patients; Stigma; Social support; Tuberculosis